Adherence to RUSA’s Guidelines for Virtual Reference Services is Below Expected in Academic Libraries - Hughes, Annie M. (Evidence Based Library and Information Practice, 2010)
Objective – To evaluate the quality of academic libraries’ virtual reference services and measure compliance to the Reference & User Services Association’s (RUSA’s) Guidelines for Virtual Reference & User Services. Design – Qualitative research study evaluating virtual reference chat sessions using RUSA’s Guidelines for Virtual Reference & User Services. Setting – Virtual reference environments in public academic libraries in the United States. Subjects – Twenty virtual reference providers from public academic libraries. Methods – Initially researchers selected 1 academic library out of each of the 50 states to evaluate for quality virtual chat reference services, however because of factors including time and availability of virtual chat services to unaffiliated institutions; the sample included only 20 academic libraries. After selecting the 20 academic libraries for evaluation, researchers posed as virtual chat reference patrons using emails and aliases that had no affiliation to any particular institution. Researchers then asked the librarian or library staff a two-part question making sure to leave out any library jargon or anything that would lead the virtual chat reference operator to recognize that they are also affiliated with a library or library school. Using the RUSA Guidelines for Virtual Reference & User Services, researchers then evaluated their virtual chat reference experience for the following: Approachability; Interest; Listening/Inquiring; Searching; Follow-Up; Suggests patron call or visit the library. Main Results – When evaluated for jargon-free websites and overall usability in finding all types of reference services, 80% of the library’s websites were easy to use and jargon free, reflecting overall high usability. Evaluation of library staff’s ability to maintain “word contact” by writing prompts to convey interest in the patron’s question left some room for improvement. Sixty percent of researchers coding their virtual reference experience thought the level of contact was below expected. Information regarding question and answering procedures, question scope, types of answers provided and expected turnaround time for questions was only available in 30% of examined websites. Thirty-five percent of researchers felt that library staff members gathered enough information to answer the question without compromising privacy, however, 25% thought that staff members gathered a very small amount of information on the patron’s need, although privacy never felt compromised. When researchers evaluated the library staff member on their ability to explain how to utilize resources properly, 50% thought the instruction provided was below average. Although 15% believed they received “superior instruction.” Seventy-five percent of the researchers were not asked by a library staff member if the question received an adequate answer, 50% of reference transactions library staff did not consult a librarian or expert, and in 55% of transactions the staff member did not suggest that the patron visit or call the library. Conclusion – While the researchers received some valuable information about the need to improve virtual reference services in academic libraries, there were some flaws in their research. The question they developed was almost too clear and made it difficult for the individual answering the chat reference to adequately perform a reference interview or ask probing questions. It is possible that because researchers carefully planned out their question they set themselves up to create an interaction that would not normally occur in a virtual chat reference environment. Also, because researchers were unable to evaluate what was occurring in the environment surrounding the virtual chat reference providers it was impossible to make a judgment on the speed or length of the interaction. The researchers did come away from the study with results that point to a need to utilize the RUSA guidelines in order to conduct effective reference interviews, maintain appropriate contact with the user when engaging in chat reference, provide instruction and point patrons to quality resources as well as consult an expert on the topic if needed. They surmised that if libraries utilized these guidelines, virtual chat reference services would be improved.